OPTIMAL STOCK PORTFOLIO USING SINGLE INDEX MODEL (Case Study: 50 Biggest Market Capitalization listed on the Indonesia Stock Exchange for the Period January 2023 – December 2023) - Ridho Jatmiko Utama; Bekman Siagian (CV. Radja Publika, 2025)
By using a single index model on companies included in the group of 50Biggest Market Capitalizationwhich is listed on the Indonesia Stock Exchange from January 2023 to December 2023. This research aims to determine the ideal stock portfolio proportions. The analysis results show that two shares, PT. Chandra Asri Pacific Tbk (TPIA) and PT. Dian Swastika Sentosa Tbk (DSSA), can be included in an ideal stock portfolio.The proportion of the two issuers is 39.58% and 60.42%. From the two issuers, the return from the optimal stock portfolio is 7.37% with a risk to be borne of 20.42%.